Microstructure and mechanical properties of metal foams fabricated via melt foaming and powder metallurgy technique: a review - Parveez, Bisma; Jamal, Nur Ayuni; Anuar, Hazleen; Ahmad Nor, Yusilawati; Aabid, Abdul; Baig, Muneer (MDPI, 2022)
Metal foams possess remarkable properties, such as lightweight, high compressive strength, lower specific weight, high stiffness, and high energy absorption. These properties make them highly desirable for many engineering applications, including lightweight materials, energy-absorption devices for aerospace and automotive industries, etc. For such potential applications, it is essential to understand the mechanical behaviour of these foams. Producing metal foams is a highly challenging task due to the coexistence of solid, liquid, and gaseous phases at different temperatures. Although numerous techniques are available for producing metal foams, fabricating foamed metal still suffers from imperfections and inconsistencies. Thus, a good understanding of various processing techniques and properties of the resulting foams is essential to improve the foam quality. This review discussed the types of metal foams available in the market and their properties, providing an overview of the production techniques involved and the contribution of metal foams to various applications. This review also discussed the challenges in foam fabrications and proposed several solutions to address these problems.